In vitro antitumor activity of endophytic and rhizosphere Gram-positive bacteria from Ibervillea sonorae (S. Watson) Greene against L5178Y-R Lymphoma cells - Romero Arguelles, Ricardo; Romo Sáenz, César Iván; Morán Santibáñez, Karla; Tamez Guerra, Patricia; Quintanilla Licea, Ramiro; Orozco Flores, Alonso Alberto; Ramírez Villalobos, Jesica María; Tamez Guerra, Reyes Silvestre; Rodríguez Padilla, Cristina; Gomez Flores, Ricardo (Multidisciplinary Digital Publishing Institute, 2022)
Plant-associated microorganisms represent a potential source of new antitumor compounds. The aim of the present study was to isolate endophytic and rhizosphere Gram-positive bacteria from Ibervillea sonorae and produce extracts with antitumor activity. Methanol and ethyl acetate extracts were obtained from 28 d bacterial fermentation, after which murine L5178Y-R lymphoma cells growth inhibition was evaluated at concentrations ranging from 15.62 µg/mL to 500 µg/mL by the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide reduction colorimetric assay. IC50 and the selectivity index (SI) were calculated and compared with healthy control human peripheral blood mononuclear cells (PBMC). Identification of the isolated strains was performed using the 16S ribosomal gene and by MALDI-TOF MS mass spectrometry. The endophytic and rhizosphere bacterial extracts from strains ISE-B22, ISE-B26, ISE-B27, ISS-A01, ISS-A06, and ISS-A16 showed significant (p < 0.05) L5178Y-R cell growth inhibition, compared with an untreated control. The rhizosphere Micromonospora echinospora isolate ISS-A16 showed the highest (90.48%) percentage of lymphoma cells growth inhibition and SI (19.1) for PBMC, whereas the Bacillus subtilis ISE-B26 isolate caused significant (p < 0.01) growth inhibition (84.32%) and a SI of 5.2. Taken together, results of the present study evidenced antitumor effects by I. sonorae endophytic and rhizosphere bacteria culture extracts. Further research will involve the elucidation of the compounds that exert the antitumor activity and their evaluation in pre-clinical studies.